Improving Quality of Election Process Using Crowdsourcing Techniques - Blerim REXHA; Ilir MURTURI; Isak SHABANI; Avni REXHEPI (International Journal of Applied Methods in Electronics and Computers, 2016)
Quality of election process is a main factor for acknowledging the general election results. In this sense a feedback from voters is critical to maintain a desired process quality. Crowdsourcing is establishing as standard platform to capture feedback and new ideas from the participating stakeholders. This paper presents an efficient solution using crowdsourcing techniques for improving the quality of election processes through a simple feedback web form in polling stations. These polling stations are securely connected to Central Election Commission monitoring room, where the overall quality in national scale can be monitored. The survey conducted with more 600 respondents shows that this approach will be acceptable from citizens and will improve the total quality and acceptance of election results.